Birth weight and autism spectrum disorder: A population‐based nested case–control study. Issue 4 (13th January 2020) - Talmi, Ziv; Mankuta, David; Raz, Raanan
Abstract : Low birth weight (<2, 500 g) and preterm birth (<37 weeks) were found to be associated with increased risk of autism spectrum disorder (ASD), however, the data regarding the entire birth weight (BW) and gestational age (GA) range are inconclusive. In this population nested case–control study, based on the Israeli National Insurance Institute records, we aimed to estimate the associations in the Israeli population. The study population included all children born between 2000 and 2012 and diagnosed with ASD ( N = 12, 635 cases), and a random 20% sample of children born in the same period who were not diagnosed with ASD ( N = 369, 548 controls). We used multiple logistic regression models to calculate the risk of ASD for each BW and GA category, adjusted for covariates (child sex, maternal age, paternal age, population group, maternal wage, paternal wage, having a sibling with ASD, multiple gestation and socioeconomic status). BW < 3, 000 g and GA < 39 weeks were associated with higher risk of ASD, including BW of 2, 500–3, 000 g (adjusted odds ratio [AOR], 1.18; 95% CI, 1.12–1.24, in comparison to the 3, 000–3, 500 g category) and GA of 37 & 38 weeks (AOR, 1.35; 95% CI, 1.25–1.45 and AOR, 1.13; 95% CI 1.06–1.20, respectively; in comparison to GA of 40 weeks). To account for the high correlation between GA and BW, we modeled BW percentiles for gestational age and found that the BW < 20th percentile was associated with an increased risk of ASD (AOR, 1.10; 95% CI, 1.01–1.19). These results demonstrate that associations of ASD with BW and GA are not limited to commonly used clinical cutoffs. Autism Res 2020, 13: 655–665 . © 2020 International Society for Autism Research, Wiley Periodicals, Inc. Lay Summary: Autism spectrum disorder (ASD) has been associated with low birth weight (<2, 500 g) in prior research. Our study aims to describe the relationship between birth weight (BW) and ASD in the Israeli population. We found that BW <3, 000 g was associated with a higher risk of ASD. These results demonstrate that an increased risk of ASD is not confined to clinically defined cutoffs such as BW < 2, 500 g.